Reimagining Sugioka Osteotomy: A Paradigm Shift in the Treatment of Avascular Necrosis of the Femoral Head - Hrishikesh Saodekar; Yogesh Salphale; Gopal Shinde; Sushrut Babhulkar (Trauma Case Reports)
Background: Osteonecrosis, also known as avascular necrosis (AVN), of the femoral head is a debilitating condition characterized by the death of bone tissue due to a lack of blood supply. Surgical interventions, particularly osteotomies, are critical in the management of osteonecrosis, especially in its pre-collapse or early stages. We propose a modified version of this osteotomy, which offers a potential for salvaging the femoral head in early cases of AVN of the hip, up to stage 2A, 2B, or early stage 3 (Ficat and Arlet).